2016
DOI: 10.1371/journal.ppat.1006039
|View full text |Cite
|
Sign up to set email alerts
|

The CXCL12/CXCR4 Signaling Pathway: A New Susceptibility Factor in Human Papillomavirus Pathogenesis

Abstract: The productive human papillomavirus (HPV) life cycle is tightly linked to the differentiation and cycling of keratinocytes. Deregulation of these processes and stimulation of cell proliferation by the action of viral oncoproteins and host cell factors underlies HPV-mediated carcinogenesis. Severe HPV infections characterize the wart, hypogammaglobulinemia, infection, and myelokathexis (WHIM) immunodeficiency syndrome, which is caused by gain-of-function mutations in the CXCR4 receptor for the CXCL12 chemokine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 72 publications
(92 reference statements)
4
29
0
3
Order By: Relevance
“…Although background staining was higher than we would have liked using this antibody, the conclusion was supported by digital scanning across the length of the raft tissue (S7C Fig). In contrast to the situation in undifferentiated monolayer cells however, the detectable E2 protein seen in the differentiated raft cultures was predominantly nuclear in our hands, although previous studies have reported both nuclear and cytoplasmic E2 protein using this antibody [63]. In an attempt to substantiate these observations, we next went on to examine E2 by western blotting (S7D, S7E and S7F Fig), using the microdissection approach used previously to assess L1 accumulation.…”
Section: Resultsmentioning
confidence: 52%
“…Although background staining was higher than we would have liked using this antibody, the conclusion was supported by digital scanning across the length of the raft tissue (S7C Fig). In contrast to the situation in undifferentiated monolayer cells however, the detectable E2 protein seen in the differentiated raft cultures was predominantly nuclear in our hands, although previous studies have reported both nuclear and cytoplasmic E2 protein using this antibody [63]. In an attempt to substantiate these observations, we next went on to examine E2 by western blotting (S7D, S7E and S7F Fig), using the microdissection approach used previously to assess L1 accumulation.…”
Section: Resultsmentioning
confidence: 52%
“…Importantly, HPV-mediated keratinocyte transformation required HPV oncogene E6- and E7-enabled signaling through the CXCL12-CXCR4 WHIM axis. Conversely, a recent study indicated that CXCR4 WHIM promotes stabilization of E6 and E7 in differentiated keratinocytes [52]. While CXCR4 itself did not promote keratinocyte proliferation, HPV-infected keratinocytes expressing CXCR4 WHIM receptors demonstrated increased proliferation compared to infected cells with wild type CXCR4.…”
Section: 3 Immunopathogenesismentioning
confidence: 95%
“…Since WHIM patients respond less robustly to vaccination than normal individuals (see below), whether or not HPV vaccination will offer similarly effective protection to genital types is not currently known but the favorable risk‐benefit profile strongly favors vaccination of WHIM patients of both sexes prior to likely exposure. Previous in vitro experimental data have implicated expression of the mutant WHIM CXCR4 receptor on keratinocytes as a factor in wart development and possible progression to malignancy . While this may play a role, several lines of evidence point to the primary defect in WHIM patients being a lack of immune response to the virus: (a) anecdotal evidence suggests that some lesions can regress after immune stimulatory therapies, (b) a patient who spontaneously lost her WHIM allele in the myeloid compartment cleared her lesions, and (c) lesions can regress after patients are treated with anti‐CXCR4 drugs .…”
Section: Wartsmentioning
confidence: 99%